Building façade cladding detachment: A case study - Lordsleem Jr., Alberto Casado; Faro, Humberto Faro (Revista ALCONPAT, 2017)
The detachment of ceramic tile and natural stone from building facades are a recurring cause of concern to users and construction professionals. This paper describes a facade pathology case study of ceramic and stone coverings on a 30-year-old residential building, identifying occurrences and assessing the situation. The methodology included data collection, percussion and adhesive strength tests, diagnosis, prognosis and solution. The results showed a deficiency in adhesive strength in 57% of the tests and 13% of tiles inspected had a hollow sound. The pathology description and the sequence of diagnostic definition activities are the main contributions of this study, which can help solve several problems with buildings of similar age, materials, and construction techniques.